2002
DOI: 10.1046/j.1365-2141.2002.03798.x
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus induces a direct inhibitory effect on antigen presentation by monocyte‐derived immature dendritic cells

Abstract: Summary. The hypothesis that productive infection of monocyte-derived immature dendritic cells (DCs) by the human cytomegalovirus (HCMV) is associated with decreased immunostimulatory capacity was tested in this study. DCs were infected with 60-80% efficiency by HCMV strain TB40/E. Infected versus uninfected cells were analysed by fluorescence-activated cell sorting and by immunocytochemistry for surface expression of major histocompatibility complex (MHC) and co-stimulatory molecules as well as cytokine secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
69
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 29 publications
4
69
0
1
Order By: Relevance
“…A number of studies have suggested that the virus may aggravate immunodeficiency by interfering with antigen presentation. [2][3][4][5][6][7] In these publications, dendritic cells (DCs) have been generated from monocytes or CD34 ϩ bone marrow progenitor cells after 5 to 12 days of cytokine-supplemented culture. Such monocyte-derived DCs (moDCs) or bone marrowderived Langerhans cells are highly potent stimulators of T-cell activation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have suggested that the virus may aggravate immunodeficiency by interfering with antigen presentation. [2][3][4][5][6][7] In these publications, dendritic cells (DCs) have been generated from monocytes or CD34 ϩ bone marrow progenitor cells after 5 to 12 days of cytokine-supplemented culture. Such monocyte-derived DCs (moDCs) or bone marrowderived Langerhans cells are highly potent stimulators of T-cell activation.…”
Section: Introductionmentioning
confidence: 99%
“…First, major histocompatibility complex (MHC) class I and class II and costimulatory molecules are down-regulated, resulting in impaired antigen presentation and increased susceptibility to natural killer cell-mediated lysis. [2][3][4][5][6][7][8] Second, a virally induced, soluble immunosuppressive factor released by mature moDCs has been postulated by several groups and was recently identified as CD83. 5,7 Third, infection of immature moDCs is lytic and leads to cell death.…”
mentioning
confidence: 99%
“…On the contrary, there are results that indicated some leakiness in the functions of vRAPs (40)(41)(42). However, even if infected DCs retain a residual capacity for Ag presentation, a series of additional viral mechanisms ranging from downregulation of costimulatory molecules over changes in the secretion of chemokines and cytokines to the inhibition of migration and maturation may severely impair DC functions (17,18,(43)(44)(45)(46)(47)(48)(49)(50)). Yet again, there are studies that report on host countermeasures that retain the function of DCs after CMV infection (51)(52)(53).…”
mentioning
confidence: 99%
“…They may distribute virus from peripheral entry sites towards lymphatic tissue; and infection of DC may pivotally result either in immunosuppression or in immune activation, depending on the cytopathic effect (CPE) of the virus. DCs are among the first cells encountered by viruses, and can be infected by viruses such as LCMV (23), Lassa fever virus (24,25), human cytomegalovirus (26)(27)(28), Influenza virus (29), and Measles virus (30,31). Many of them can finish complete life cycles in DCs and also produce an infectious virus.…”
Section: Discussionmentioning
confidence: 99%